(untitled) (Vietnam Journal of Community Medicine, 2026)
Abstract: To describe the prevalence of hypertension and associated factors among adults aged 40 years and older in Na Hy Commune, Dien Bien Province, in 2025. Methods: A cross-sectional descriptive study was conducted among 3,271 adults aged 40 years and older residing in Na Hy Commune, Dien Bien Province. Results: Among 3,271 residents aged 40 years and older who participated in the study, the prevalence of hypertension was 13.3%. The prevalence of hypertension increased progressively with age, being highest among individuals aged 70 years and above (31.9%) and lowest in the 40–49 age group (7.4%). The prevalence of hypertension was low among participants with chronic energy deficiency (0.3%) and those with normal BMI (7.7%), while it was markedly higher in overweight (62.3%) and obese individuals (37.0%). Analysis of associated factors showed that alcohol consumption, cigarette smoking, high salt intake, and overweight/obesity were significantly associated with a higher likelihood of hypertension, whereas regular physical activity was associated with a lower likelihood of hypertension. Conclusion: Behavioral factors and nutritional status are closely associated with hypertension, indicating the need to prioritize lifestyle modification interventions at the community level.